Síndrome de apnea hipopnea obstructiva del sueño y excesiva somnolencia diurna en la población de la parroquia El Sagrario - Celi Cárdenas, Jairo Eliceo (2019)
Obstructive sleep apnea is an underrecognized chronic disease which is associated with an increase in mortality and morbidity, inappropriately there is no data on its prevalence in our country, so it was categorical to conduct this study to stage the risk and determine the risk factors that predispose to suffer from this syndrome, additionally to establishing whether people with moderate-high risk have daytime sleepiness. It is a cross-sectional study that was carried out in the population of “El Sagrario” of Loja city. The participants were evaluated using the STOP-BANG questionnaire to determine the level of risk of obstructive sleep apnea and by the Epworth test to assess the presence of daytime sleepiness. Data were analysed using SPSS with 95% significance level. Of the 361 respondents, 63.3% (n = 228) had a low risk of obstructive sleep apnea and 21.3% (N = 77) had a high probability of developing the syndrome. Amongst the high-risk respondents, 78% (n = 60) were men and 58% (n = 45) were between 50-60 years of age. Of those who were at risk for obstructive sleep apnea, 58% (n = 45) reported having a first-degree relative with snoring. We can settle that obstructive sleep apnea is a prevalent condition in the population of the “El Sagrario” parish, it is higher in men than in women and it was observed that the High risk tends to increase with age. KEY WORDS: Sleep apnea, Stop-bang questionnaire, Epworth scale, Daytime hypersomnolence, Obesity, Obstructive sleep apnea hypopnea syndrome.